The Response of Creatine Kinase Specific Activity in Rat Pituitary to Estrogenic Compounds and Vitamin D Less-Calcemic Analogs - D. Somjen; N. Mirsky; S. Tamir; J. Vaya; G. H. Posner; A. M. Kaye (International Journal of Cell Biology)
We examined the response of rat female pituitary at different metabolic stages to treatments with estrogenic compounds and vitamin D analogs. Immature or ovariectomized (Ovx) female rats responded by increased creatine kinase specific activity (CK) to estradiol-17β (E2), genistein (G), daidzein (D), biochainin A (BA), quecertin (Qu), carboxy- G (cG), carboxy- BA (cBA), and raloxifene (Ral). The response was inhibited when Ral was injected together with the estrogens. CK was increased when hormones were injected daily into Ovx rats for 4 different time periods. Pretreatment with the less-calcemic vitamin D analogs JK 1624 F2-2 (JKF) or QW 1624 F2-2 (QW) followed by estrogenic injection resulted in increased response and sensitivity to E2 and loss of inhibition of E2 by Ral. CK was also increased by feeding with E2 or licorice or its components dose- and time- dependent in immature or Ovxrats. Diabetic female rats did not respond to increased doses of E2. In conclusion, rat female pituitary is estrogens-responsive organ, suggesting to consider its response for HRT in postmenopausal women for both beneficial and hazardous aspects.